1986
DOI: 10.1577/1548-8659(1986)6<168:cigamo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Growth and Maturity of Walleyes Associated with Stock Rehabilitation in Western Lake Erie, 1964-1983

Abstract: The precipitous decline in abundance of walleyes (Stizostedion vitreum vitreum) in western Lake Erie during the 1960s caused major concerns for the future of this resource. Mercury contamination in walleyes in 1970 resulted in a moratorium on commercial fishing in United States and Canadian waters. The opportunity arose for resource agencies to develop a plan for rehabilitation of the walleye stocks, and quota management for walleyes was begun in 1976. After 8 years, the resource had recovered dramatically and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 2 publications
1
37
0
Order By: Relevance
“…Yellow perch and walleye also provide an excellent case study of density dependence. Studies by Forney (1965Forney ( , 1971Forney ( , 1974Forney ( , 1976Forney ( , 1977a, and others (Tarby 1974, Neilson 1980, Serns 1982, Muth and Wolfert 1986, Buijse and Houthuijzen 1992 indicate these species (and congeneric pikeperch Stizostedion lucioperca and European perch Perca fluviatilis) show strong compensatory responses in growth and age at maturity to changes in mortality.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Yellow perch and walleye also provide an excellent case study of density dependence. Studies by Forney (1965Forney ( , 1971Forney ( , 1974Forney ( , 1976Forney ( , 1977a, and others (Tarby 1974, Neilson 1980, Serns 1982, Muth and Wolfert 1986, Buijse and Houthuijzen 1992 indicate these species (and congeneric pikeperch Stizostedion lucioperca and European perch Perca fluviatilis) show strong compensatory responses in growth and age at maturity to changes in mortality.…”
Section: Introductionmentioning
confidence: 94%
“…3 is based on fitting a function to values of the fraction of females mature (as determined by length), intermediate to those observed for fast and slow walleye growth periods in Lake Erie (Muth and Wolfert 1986). For typical lengths at age, 57% of age-3 yellow perch and 35% of age-5 walleye are mature.…”
Section: Spawningmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous elasmobranch studies have not addressed changes in maturity as a result of a biomass increase, several studies in teleosts have suggested that increased competition for fewer available resources can result in delayed maturation and lower reproductive potential, creating an overall compensatory shift in the population (Rose et al 2001). For example, the percentage of mature age-1 male Walleyes Sander vitreus in Lake Erie declined from 99% after drastic population depletion to 32% after the population had recovered in Lake Erie (Muth and Wolfert 1986). In addition, studies on Silver Hake Merluccius bilinearis in the northwest Atlantic Ocean suggest that sexual maturity can be delayed when stock abundance is increased due to added competition (Helser and Almeida 1997).…”
Section: Age (Years)mentioning
confidence: 99%
“…Most evidence for competition among piscivorous fishes has been indirect, such as correlations between prey density and predator growth, condition and biomass (Ploskey & Jenkins 1982;Muth & Wolfert Abstract -Competition, both intraspecific and interspecific, among piscivorous fishes (predators) may be more pronounced in reservoirs because of the artificial nature of these systems and the continuous anthropogenic influences that may not allow natural processes to regulate their densities. Most evidence for competition among piscivorous fishes has been indirect, such as correlations between prey density and predator growth, condition and biomass (Ploskey & Jenkins 1982;Muth & Wolfert Abstract -Competition, both intraspecific and interspecific, among piscivorous fishes (predators) may be more pronounced in reservoirs because of the artificial nature of these systems and the continuous anthropogenic influences that may not allow natural processes to regulate their densities.…”
Section: Introductionmentioning
confidence: 99%